Effect of Different CO2 Treatments on the Metal Leaching in Steel Slag Binders - Liu, Yaojun; Fang, Jingrui; Liu, Songhui; An, Xiaopeng; Kang, Yanwen; Wang, Lan (Frontiers in Energy Research, 2021)
Carbonation is an effective method to promote the quality of the steel slag binder. In this article, two carbonation approaches, namely hot-stage carbonation and accelerated carbonation, were employed to leach the metals, and the influence mechanism on the metal sequential leachability of the binders composed of 80 wt% of EAF slag incorporating 20 wt% of Portland cement (PC) was revealed. The carbonate products, microstructures, and chemical states were investigated, and the results indicated that chromium, vanadium, and titanium gradually transformed into inactive phases after two carbonation approaches, while zinc appeared the opposite trend. The sequential leachability of chromium declined with the increase of the carbonation efficiency, in which the exchangeable chromium decreased from 1.99 mg/kg in the A2A binder to below the detection limit in the A2C binder and C2C binder. Hot-stage carbonation treatment facilitated particle agglomeration, minerals remodeling, and calcite formation. The carbonation curing of the steel slag paste resulted in the formation of amorphous CaCO3, calcite crystalline and Si-bearing hydrates that covered the pores of the matrix, and silicate structure with a higher disorder. The hot-stage carbonation and accelerated carbonation curing methods were adopted to jointly prevent the leaching of harmful metals and facilitate promising high-volume steel slag-based binders with structural densification and CO2 storage.